Effects of clear-cutting and site preparation on water quality from a drained Scots pine mire in southern Finland - Nieminen, M. (Boreal Environment Research Publishing Board, 2024)
Ditch outflow from four treatment areas on a drained Scots pine mire was sampled for one year before and four years after clear-cutting and different site preparation operations. Ditch-mounding, or excavation of 40–60 cm deep ditches at spacings of 12–15 m in connection with mounding, is currently considered the most reliable site preparation method for drained peatlands in Finland. High leaching rates of suspended solids were detected from the ditch-mounding area, where the ditches reached down into the mineral soil below peat layer. In contrast to clear-cutting + mounding (without ditches) and clear-cutting alone, cutting and ditch-mounding also increased the leaching of ammonium and nitrate. Phosphorus concentrations in ditch outflow following clear-cutting and site preparation increased from areas where peat contents of phosphorus sorbing minerals (aluminium and iron) were low. The study demonstrated that clear-cutting and site preparation can significantly impair water quality from drained low productive pine mires.